2018
DOI: 10.3390/plants7030071
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Rapeseed Root Response to Waterlogging Stress

Abstract: The overall health of a plant is constantly affected by the changing and hostile environment. Due to climate change and the farming pattern of rice (Oryza sativa) and rapeseed (Brassica napus L.), stress from waterlogging poses a serious threat to productivity assurance and the yield of rapeseed in China’s Yangtze River basin. In order to improve our understanding of the complex mechanisms behind waterlogging stress and identify waterlogging-responsive proteins, we firstly conducted iTRAQ (isobaric tags for re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 97 publications
0
19
0
Order By: Relevance
“…Lastly, it should be noted that genotypic variation for waterlogging tolerance can exist within each species (e.g. Arduini et al, , Collaku & Harrison, for wheat; Masoni et al, , Pang et al, for barley; Xu et al, for rapeseed; Malik, Ailewe, & Erskine, for field pea); analyses of intra‐specific variation for the parameters measured here would be an interesting future study.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Lastly, it should be noted that genotypic variation for waterlogging tolerance can exist within each species (e.g. Arduini et al, , Collaku & Harrison, for wheat; Masoni et al, , Pang et al, for barley; Xu et al, for rapeseed; Malik, Ailewe, & Erskine, for field pea); analyses of intra‐specific variation for the parameters measured here would be an interesting future study.…”
Section: Resultsmentioning
confidence: 88%
“…Regarding to rapeseed, rooting length has only been studied in seedlings, having an extremely sensitive response to waterlogging, as plants of 3 DAS waterlogged for 12 hr reached ca. 50% of controls (Xu et al, ). In seedlings of field pea subjected to 12 days of waterlogging at 8 DAS, the penetration depth of roots reached 44% of controls (Przywara & Stępniewski, ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that differences between cultivars exist in respect to waterlogging tolerance, mainly in Asian cultivars (e.g., Zou et al, 2014; Xu et al, 2015, summarized in Mustroph, 2018). However, the underlying mechanisms of tolerance have not been identified yet, despite comparative analyses at the transcriptional (Zou et al, 2015; Zou, Tan, et al, 2013) and proteomic (Xu et al, 2018) level. These analyses only showed minor differences in gene expression in response to waterlogging between the two cultivars Zhongshuang 9 and GH01 (Zou et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Although the second broad group contains a relatively small number of genes, they have been retained during the evolution of cotton, implying that they may play important roles in biological processes. Regardless of whether plants are subjected to biological or abiotic stress, their initial sensing parts are basically at the roots [44][45][46]. Moreover, analysis of the gene expression in different tissues and the molecular biological functions were performed differentially [47,48].…”
Section: Discussionmentioning
confidence: 99%